Consumer Perception towards Brand Slogans:An investigative study towards Consumer Perception in the Malaysian Automobile Industry - Sharjeel, Syed Muhammad (2007)
This dissertation focuses on the concerned attribute of brand which would be the primary investigative entity of this dissertation; brand expression/ brand message/ brand tagline/brand slogan. Brand slogans are exploited as a marketing tool to facilitate message diffusion among the consumer market, as well as a powerful tool for targeted segment’s brand positioning (Cheng et al, 2006). In our every day lives, we come across hundreds of brands with several brand slogans targeting at different level of positioning towards the consumer mind. Having this in mind, this dissertation is motivated by a series of inquiries; have we ever critically analyzed these brand slogans? Are they just complimentary to a powerful brand? Do they enable the company to communicate with the consumer? Is it a viable form of marketing communications? All these questions lead to our discussion of what do these brand slogans mean to a consumer and how consumers perceive them. In this research, the previewed agenda’s will be incorporated from the perspective of the automobile industry in Malaysia. Brand slogan awareness, brand personality and consumer perceived value were tested for the brand Proton and Honda. Results achieve show significant discrepancies for the brand Proton, where as favorable and fulfilling perception towards Honda. The second phase of this dissertation tested the three constructs for the significant relationship to general consumer perception. The results state perceived social value statistically significant in impacting consumer’s perception towards brand slogan.